PENGARUH LATIHAN MASSED PRACTICE TERHADAP KEMAMPUAN CHEST PASS PADA SISWA PUTRA EKSTRAKURIKULER BOLA BASKET SMA NEGERI 1 GUNUNGSARI TAHUN PELAJARAN 2018/2019 - Wibi Priambodo; Dadang Warta Candra Wira Kusuma; Nune Wire Panji Sakti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Abstract: Basketball is a game played by two teams of five people each. The team consists of twelve players including the captain. Each team tries to score a number. This research was motivated by extracurricular male students not being able to master the chest pass technique properly, how to feed the ball is still not right, especially chest or chest pass, and the training program for basic techniques is still lacking. This study aims to determine whether through massed practice exercises can improve chest pass ability in the basketball game for male students who take basketball extracurricular activities at SMA Negeri 1 Gunungsari. The method used in this study is an experiment, this research is included in the form of one group pretest-posttest design. The population in this study were students at SMA Negeri 1 Gunungsari, while the sample was extracurricular basketball participants at SMA Negeri 1 Gunungsari, totaling 15 students. The instrument used was a wall bounch test with a validity level of 0.804 and a reliability of 0.893. The data analysis technique used is the t-test statistical analysis with hypothesis testing. The results of the analysis show that: There is a significant influence between massed practice exercises on the chest pass ability of male extracurricular basketball students at SMA Negeri 1 Gunungsari. From the t test data it can be seen that t-count (4,561)> t-table (2,145), then there are significant differences in the level of chest pass ability. The results of the study and discussion can be concluded that there is an effect of massed practice exercises on the ability of chest passes in male basketball extracurricular students at SMA Negeri 1 Gunungsari.